Macronutrients intake of top level cyclists during continuous competition--change in the feeding pattern - Garcia-Roves, P. M.; Terrados, N.; Fernandez, S. F.; Patterson, A. M (International Journal of Sports Medicine, 1998)
In order to quantify the nutritional status and the feeding pattern of professional cyclists during continuous competition, food intake was accurately measured and recorded using the weighed inventory of food (over three 24 h periods) during all meals in ten top professional cyclists during a real 3 weeks' competition. A 24 h period was defined as the time between the start of one stage and the next start. The 24 h period intake of energy, protein, fat, and carbohydrate was used to discover whether these intakes met requirements for endurance exercise. The average intake of energy and macronutrients was: energy = 23.5 +/- 1.8 MJ/24 h period, carbohydrate = 841.4 +/- 66.2 g/ 24h period; protein = 201.8 +/- 17.7g/24 h period; and fat = 158.6 +/- 16.3 g/24 h period. The carbohydrate, protein and fat contribution to energy was 60.0%, 14.5%, and 25.5% respectively. Fluid intake per 24h period was 3.29 +/- 0.94l (1.26 +/- 0.55 l during the race). Our study shows a similar energy intake in comparison with the only previous study in 1989 but there is a change in the feeding pattern of top level cyclists. A more important role is given to the intake of carbohydrate just after competitions together with an increase in protein intake. Both changes could have a positive effect on performance.